Author Correction: The Brainlat Project, a Multimodal Neuroimaging Dataset of Neurodegeneration from Underrepresented Backgrounds (Scientific Data, 2023 10 1 889 10.1038/S41597-023-02806-8) - Garcia-Serrano, A (Nature Research, 2024)
Correction to: Scientific Data, published online 09 December 2023 In this article the author name Maria Isabel Behrens was incorrectly written as Maria Isabel Beherens. The original article has been corrected. © 2024, The Author(s).